Optimization of Coconut Fiber and Styrofoam Composition in Concrete to Improve Strength and Sound Absorption - Purwanto; Ferry Firmawan; Fahrudin Ahmad; Hani Purwanti; Aimmatul Husna; Nadirah Darus; Zaiton Haron; Khairulzan Yahya (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study aimed to evaluate the effect of coconut husk and Expanded Polystyrene (EPS) composition on the mechanical and acoustic properties of lightweight concrete. The research was conducted experimentally using a two-way factorial design with coconut husk variations of 0%, 0.5%, 1%, 1.5%, and 2% of cement weight and EPS variations of 0%, 10%, 20%, and 30% of coarse aggregate volume. A total of 20 mix variations (5 coir levels × 4 EPS levels) were prepared with three replications for each test, resulting in 120 specimens. Compressive strength was tested at 7 days following ASTM C39, while sound absorption was measured at frequencies of 100–2000 Hz based on ISO 10534-2. The results showed that the addition of coconut husk up to 1% improved compressive strength through fibre reinforcement, whereas increasing EPS content enhanced sound absorption due to higher porosity but reduced mechanical strength. Statistical analysis using ANOVA (R² = 0.94, p < 0.05) and desirability optimisation identified the optimal composition at 1% coconut husk and 10% EPS. The developed lightweight concrete is suitable for non-structural building components requiring improved acoustic performance and reduced weight.